Comparative Study on the Axial Compression and Bearing Capacity of Reactive Powder Concrete-Filled Circular Steel Tube - Mingyang Chen; Xiaomeng Hou (Advances in Materials Science and Engineering)
Reactive powder concrete (RPC) was confined by the circular steel tube to obtain the required ductility. The axial compression test results of 139 columns from different scholars were collated and compared to study the axial compression and bearing capacity of a reactive powder concrete-filled circular steel tube, of which the confining coefficient is 0.057–2.312 and the RPC strength is 76.6–178.2 MPa. Load-displacement curves have been categorized into four stages: (1) elastic; (2) elastic-plastic; (3) descending; and (4) strengthening. The failure mode can be divided into three types according to the different confining coefficients as (1) wall buckling; (2) diagonal shear; and (3) drum-shaped. The confining coefficient, core RPC strength, steel fiber volume, steel tube D/t ratio, and loading mode on the ultimate bearing capacity were analyzed. The results showed the confining coefficient to be the main factor affecting ultimate bearing capacity. The equation for determining ultimate bearing capacity was established based on the limit equilibrium theory, with the lateral confining coefficient of RPC (k) determined to be 2.86, less than that of normal concrete at 4.1. Based on the experimental analysis results and China’s “Design and Construction Code for Concrete-Filled Steel Tube Structure” (CECS 28-2012), the design proposal for an RPC-filled steel tube was recommended.